The Medical Record: Narration and Story as a Path Through Patient Data - Kluge, E.-H. W. (Methods of Information in Medicine, 1996)
Kay and Purves' proposed narratological model of the medical record is based on the familiar phenomenological insight that the perception of data is conditioned by the conceptual framework of the perceiver. Unfortunately, unless handled very carefully, this approach will make the significance of a medical record unique to the person who constructed it and impermeable to outside scrutiny. However, when integrated into the analog-model of the medical record, the narratological model can be accommodated as the clinician-relative construction of a patient profile within the data that make up the medical record. Some implications for the construction of expert systems and competence analysis are indicated.
Keywords: Medical Record; Theoretical Models; Patient Profile; Narrative